Упростите : 1) cos 2a/cosa+sina-cosa 2)(ctga+tga)*sin2a

Упростите : 1) cos 2a/cosa+sina-cosa 2)(ctga+tga)*sin2a
Гость
Ответ(ы) на вопрос:
Гость
1)  cos2α/cosα +sinα - cosα =(cos²α - sin²α +sinα*cosα -cos²α)/cosα= = (sinα*cosα -sin²α)/cosα =sinα -sinα*tqα =sinα(1 -tqα)  или tqα(cosα - sinα). 2) (ctqα + tqα)*sin2α =(cosα/sinα +sinα/cosα)*2sinα*cosα =2(cos²α +sin²α) =2. ******************************************************************************************** 1) cos2α/cosα +sinα - cosα =(cos²α -sin²α)/cosα +sinα -cosα = = cαsα - sinα*tqα +sinα -cosα = sinα -sinα*tqα =sinα(1- tqα).
Не нашли ответ?
Ответить на вопрос
Похожие вопросы